Exploring Project-based Learning in the Public High Schools in Nepal - Acharya, Milan (Spandan, 2023)
This research seeks to examine the application of Project-Based Learning (PBL) within public high schools across Nepal, focusing on health and population education. This study aims to assess perceptions, practices and challenges of such integration into the establishment. In an interpretative paradigm, techniques such as interviews, focus group discussions and classroom observations are used to collect data. The study sample comprises five health and population teachers from Kirtipur municipality who were selected due to their experience and active involvement in teaching and professional development. Findings reveal that PBL strongly falters due to limited resources, inadequate materials, infrastructure and funding. PBL tend to be adopted more by urban schools as compared to rural ones due to resources access advantage. Other challenge includes lack of harmonization between PBL activities and the national curriculum, too few teacher training opportunities and very large classes. However, teachers, when pressed, admitted to the development which PBL brings about in one's critical thinking, teamwork and practical learning, but now have difficulty implementing it due to more time restrictions and syllabus completion pressure. Despite that, it enhances student engagement and develops hard-learned skills. Resource gaps, professional development, and stakeholder awareness could promote effective PBL practices in the public school sector in Nepal.